Effect of SCnP Financial Performance on Third-Party Funds Growth in Indonesian Islamic Banks (2017-2023) - Nur'aini, Aninda; Purnamasari, Femei; Nurmalia, Gustika (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
This study aims to examine the effect of Islamic banking financial performance on the growth of Third Party Funds (TPF) in Indonesia in the period 2017–2023 using the Sharia Conformity and Profitability (SCnP) approach. This study focuses on three independent variables, namely the Islamic Investment Ratio (IIR), Islamic Income Ratio (IsIR), and Return on Assets (ROA). This study answers the gap in previous studies that rarely combine the balance between sharia compliance and profitability in explaining TPF growth. The method used is quantitative with panel data analysis using the Fixed Effect Model (FEM) on a sample of seven Islamic Commercial Banks (BUS) in Indonesia. The estimation results show that IIR (p = 0.5913) and IsIR (p = 0.9954) do not have a significant effect on TPF growth. On the other hand, ROA (p = 0.0096) has a positive and significant effect, indicating that bank profitability has a stronger influence on public trust and fund placement decisions than sharia compliance indicators. These findings suggest that while compliance with sharia principles is important, people still prioritize financial outcomes when choosing where to save their money. Therefore, Islamic banks are advised to maintain operational efficiency while strengthening sharia-based investment structures to increase credibility and competitiveness.